Letter (copy) : Spanish seamen - Tewson, Vincent
025a-0098-001 Secretary's. HVT/FC/EK/1129. 11th May, 1939. Senor J. Lizaso, Basque Delegation, 14, Eccleston Square, London, S.W.1. Dear Senor Lizaso, SPANISH SEAMEN. I am very sorry to receive your letter of the 9th instant and to learn of the difficulties which you had with the four men from Cardiff and one from London. I have today communicated with Cardiff informing them of the position and stating that so far as we are concerned any further claims that they may desire to bring must be disregarded. I quite appreciate that you did what you thought best under the circumstance, but on the whole it might have been better if it had been possible to completely ignore the men's claims. I am just afraid that if they are going round Cardiff with this money in their pockets it may have an unsettling influence there. I am hoping, however, that my letter to Cardiff will have the desired effect. Yours sincerely, Assistant Secretary. 292/946/25a/98